2008
DOI: 10.1111/j.1472-8206.2008.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the anti‐inflammatory and analgesic effects from an extract of Aplysina caissara, a marine sponge

Abstract: A variety of biologically active compounds with pharmacological applications has been reported to occur in marine sponges. The present study was undertaken to provide a set of data about an extract from Aplysina caissara, a Brazilian marine sponge. The antinociceptive and anti-inflammatory effects were investigated against different experimental models in mice. When evaluated against writhing test intraperitoneally (60 and 90 mg/kg), the extract significantly inhibited abdominal constriction by 33.7% and 41.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 36 publications
(47 reference statements)
2
15
0
Order By: Relevance
“…After filtration, the extracted material was concentrated in a rotary evaporator (Fisaton, Brazil) and the final extract was partitioned against hexane (1 : 1 v/v). The final extract was dried in SpeedVac (SPD1010; ThermoSavant, NY, USA) 13 .…”
Section: Extract Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…After filtration, the extracted material was concentrated in a rotary evaporator (Fisaton, Brazil) and the final extract was partitioned against hexane (1 : 1 v/v). The final extract was dried in SpeedVac (SPD1010; ThermoSavant, NY, USA) 13 .…”
Section: Extract Preparationmentioning
confidence: 99%
“…The specie A. caissara, an endemic Brazilian specie of marine sponges, is rich in active peptides and alkaloids 21,22 . Our laboratory studies have indicated that aqueous extracts of A. caissara, administered intraperitoneally show antinociceptive and anti-inflammatory profiles 13 . Besides, the anti-tuberculosis and cytotoxic activity was also shown in vitro 22 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Marine sponges are rich sources of pharmacological compounds [4]. Studies show that secondary metabolites of sponges play an important role in their survival in the marine water [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some compounds have been entered into clinical trials as anticancer drug candidates, including eribulin mesylate (E7389) in a phase III trial, and E7974 (hemiasterlin) in phase I trial (Mayer et al, 2010). Some extracts or compounds from marine sponges have been reported to inhibit the inflammation processes, including an ethyl acetate fraction from Cliona celata (Yang et al, 2010), the extract from Aplysina caissara (Azevedo et al, 2008), halichlorine (Tsubosaka et al, 2010), and heteronemin (Schumacher et al, 2010). We have demonstrated the anti-inflammatory potential of epimuqubilin A, a norsesterterpene peroxide isolated from marine sponge Latrunculia sp.…”
Section: Introductionmentioning
confidence: 99%